Periodicals & irregular serials - The Editors, - (Nordic Archaeological Abstracts - NAA, 1982)
Journals with papers abstracted in this number of NAA are listed here. The names and places given are those of the editors, not of the publishers or distributors (with a few exceptions). Addresses to the editor or publisher may be obtained by contacting the sub-editor or the members of the editorial board.